ANALISA PENYEBAB KEPUASAN KERJA YANG DIAKIBATKAN OLEH ETIKA KEPEMIMPINAN DAN KOMITMEN ORGANISASI KARYAWAN PT ECOSIF MULTI KREASI - Megaster, Tekni; Puspitasari, Ria (Dynamic Management Journal, 2018)
The purpose of this study was to analyze the Causes of Job Satisfaction Involved by Leadership Ethics and Organizational Commitment of Employees. The design of this study is a descriptive study that describes the information and characteristics of the population or phenomenon being studied. The description used is for statistical calculation, whereas survey investigation is conducted to measure the variables with questionnaires spread by 18 questions using five points LIKERT SCALE. The method used to evaluate the survey results of several studies with regression, primary data collected from the respondents and also secondary data to support information. From the results of this study indicate that there is a positive and significant relationship between leadership ethics, organizational commitment and employee job satisfaction. Data analysis used in this study is SPSS. The results of this study conclude that leadership ethics has a certain influence on organizational commitment and employee job satisfaction. Keywords: Leadership Ethics, Organizational Commitment, Employee Job Satisfaction.